2019
DOI: 10.3390/nu11051154
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Collagen Peptide Supplementation and Resistance Exercise Training Affects Body Composition in Recreationally Active Men

Abstract: We aimed to determine the effects of long-term collagen peptide (CP) supplementation and resistance exercise training (RET) on body composition, strength, and muscle fiber cross-sectional area (fCSA) in recreationally active men. Fifty-seven young men were randomly and double-blinded divided into a group receiving either collagen peptides (COL, 15 g/day) or a placebo (PLA). Strength testing, bioimpedance analysis, and muscle biopsies were used prior to and after an RET intervention. Food record protocols were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(69 citation statements)
references
References 50 publications
2
66
0
1
Order By: Relevance
“…In a study supporting our research results, a resistance exercise model with an intensity of 65-80%, which included 6 exercises for 5 days a week for 8 weeks, was found to cause significant changes in body fat percentage, fat weight and BMI values (Kim et al, 2016). In another study, it has been shown that resistance exercises which are applied 3 days a week for 12 weeks increase the body weight in active individuals for recreational purposes (Kirmse, Oertzen-Hagemann, de Marées, Bloch, & Platen, 2019). It is emphasized that 12 weeks of combined exercises (aerobic + resistance) applied to middle-aged obese women lead to positive improvements in body composition (Cho et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…In a study supporting our research results, a resistance exercise model with an intensity of 65-80%, which included 6 exercises for 5 days a week for 8 weeks, was found to cause significant changes in body fat percentage, fat weight and BMI values (Kim et al, 2016). In another study, it has been shown that resistance exercises which are applied 3 days a week for 12 weeks increase the body weight in active individuals for recreational purposes (Kirmse, Oertzen-Hagemann, de Marées, Bloch, & Platen, 2019). It is emphasized that 12 weeks of combined exercises (aerobic + resistance) applied to middle-aged obese women lead to positive improvements in body composition (Cho et al, 2018).…”
Section: Discussionsupporting
confidence: 80%
“…This supposition is supported by data showing that gelatin supplementation increased collagen content in engineered ligaments [126]. Similar mechanisms may also underlie muscle functional responses, specifically muscle strength, where studies have shown collagen peptide supplements to have no effect on maximal voluntary contraction [29,128], but did speed-up recovery of countermovement jump performance following strenuous exercise [29]. Since ECM degradation can occur following exercise [131], it is plausible that the purported collagen-induced ECM remodelling (e.g., increased collagen synthesis) occurred, therein improving fast/reactive movements that have a heavy tendon component (i.e., countermovement jump) [128].…”
Section: Skeletal Musclementioning
confidence: 90%
“…The ability of collagen supplementation to potentiate exercise-induced muscle adaptations is more widely studied than the effects of collagen supplementation alone yet remains contentious with mixed results depending on the outcome measure. In regards to body composition, Kirmse et al [128] observed an increase in fat-free mass after 12 weeks of RET plus 15 g/d collagen peptide supplementation, which was not observed in the placebo group. However, similar changes in cross-sectional area and muscle thickness across the whole cohort (i.e., both groups) suggest that greater myofiber hypertrophy cannot explain these changes.…”
Section: Skeletal Musclementioning
confidence: 98%
See 2 more Smart Citations